Oso Polar - Grant, Álvaro (My University, 2014)
El tema de este recurso es la locomoción animal del oso polar. Se trata de un interactivo para que el usuario pueda entender cómo se desplaza este animal.

The topic of this resource is the polar bears locomotion. It consists of an interactive infographic that helps the user understand how this animal moves.
Keywords: Infografía; Interactivo; Oso polar; Locomoción